Performance of TEG integrated channel with area expansion by using advanced passive techniques - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2021)
In this study, flow separation effects on the power generation and conversion efficiency of a thermoelectric generator integrated channel flow with area expansion are numerically studied. Impacts of using an eccentric conic object near the thermoelectric device on the performance enhancement of the system are explored with numerical simulation using finite element method. Hybrid nano sized particles are also included in the heat transfer fluid to improve thermal transport features of the base fluid. Impacts of Reynolds number (between 200 and 1000), expansion ratio of the channel (between 0.25 and 0.6), aspect ratio (between 0.1 and 1.5), location (between -1 and 5) and size (between 0.05 and 0.25) of the eccentric cone and solid nanoparticle volume fraction (between 0 and 0.02) on the fluid flow and generated power characteristic are numerically studied. It is observed that the vortex behind the step extends over the thermoelectric device surface at the highest Reynolds number while vortcies are also established behind the eccentric cone. When the expansion ratio is increased, thermo electric device power reduction is observed while the amounts are 34% and17.8% for cases at R-1 =0.25 with Reynolds number of 200 and 1000 as compared to upper channel with R-1 =0.6. The conversion efficiency also rises with higher expansion ratio while the pressure coefficient has its lowest values at R-1 =0.4. When the cone aspect ratio, size and its horizontal location from the step are increased, resizing of the vortex behind the upper channel step is observed while more fluid deflection toward the thermoelectric device is obtained. Therefore, the power of the device is increased and the power enhancement is in the range of 10%-12% for varying size and aspect ratio of the cone while it is up to 20% for different horizontal locations of the cone. There is significant enhancement in the pressure drop with higher size and aspect ratio of the conic object even though the conversion efficiency rise. However, changing the object location is favorable as compared to increasing the size and aspect ratio of the cone on the power generation, conversion efficiency and pressure drop features. The potential in the device power enhancement with nanoparticle inclusion is higher for lower Reynolds number and lower higher expansion ratio while up to 18% increment of the power is obtained with nanoparticle inclusion at the highest amount. Conversion efficiencies also rise while pressure drop slightly vary with higher solid nanoparticle volume fractions. A predictive model based on artificial neural networks has been developed that estimates the power generated in the thermoelectric device accurately and fast as compared to high fidelity three dimensional computational fluid dynamics simulations.
Keywords: Thermoelectric; Backward facing step; Eccentric cone; Finite element method; Hybrid nanofluid